Peran Konstitusi dalam Membentuk Tata Negara yang Demokratis - Suhaiy Batul Aslamiyah Nst; Zainal Abidin Pakpahan (Journal on Education, 2024)
The constitution maintains a balance of power between state institutions and prevents domination that has the potential to damage the constitutional system The importance of the constitution in maintaining political stability and national security, as well as in forming a strong foundation for economic and social development. A democratic constitution must be able to accommodate the changing and evolving times, and provide space for inclusive participation and representation. The Constitution serves as the legal basis that governs the structure and functioning of the State, as well as guarantees freedoms and human rights. Through its mechanisms, the constitution can ensure free and fair elections, inclusive political participation, and balanced power-sharing. The Constitution guarantees freedoms and human rights by establishing a list of rights guaranteed to every citizen.These rights include freedom of opinion, religion, association, as well as the right to legal protection and privacy. The constitution also protects individuals from abuse of power by the government through a balanced division of powers between the institutions of the State. The constitution also provides for oversight mechanisms over the government, such as independent watchdogs, to ensure that individual rights are not violated. A democratic constitution should provide space for people’s active participation in the political process, as well as provide a solid foundation for economic and social development. Thus, the public can be actively involved in the political process and the State can achieve sustainable political stability. The Constitution plays a very important role in promoting a transparent, accountable, and corruption-free government, with a strong foundation to ensure the integrity and sustainability of a government that is accountable to the people. With the principle of accountability, the constitution ensures that the government operates.Transparently and accountably for his actions. The constitution encourages a government free from corruption and ensures fair and efficient use of public resources